Social Sanction: Naked Parade and Vigilantism as Legal Violation Criminal Law Perspective and Human Rights - Kuswardani kuswardani; Sunaryo Sunaryo (Fiat Justisia: Jurnal Ilmu Hukum, 2021)
Naked parade and vigilantism are social sanctions or informal sanctions imposed by the community for acts deemed contrary to the local community's norms. These sanctions include vigilante action, which breaks the law. This paper aims to explain social sanctions (naked parade) from a legal perspective, particularly studied from human rights and criminal law. The study uses a normative approach so that the data sources include legal documents, references, and journals relevant to the problem being studied. The data analysis using consists of human rights principles and criminal law. The study results show that naked parade and vigilante as social sanction contradict human rights principles (liberty, non-discrimination, dignity, humanity, and equity). This act is also a criminal act, considering that the criminal law functions to protect the legal rights of individuals, the community, and the state. There is no explicit formulation of naked parade in the Penal Code (KUHP) or regulations outside the Penal Code. It is necessary to formulate it explicitly as an act that can be punished.